Classic action recognition of cross-country skiing sports combining ant colony and clustering algorithm - Yu, H.; Li, Y. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background As one of the oldest sports events in world sports history, cross-country skiing involves basic techniques such as mountaineering, skiing, and gliding, covering multiple classic actions during the process.